Surgical navigation in paediatric orthopaedics. Issue 5 (May 2016) - Docquier, Pierre-Louis; Paul, Laurent; TranDuy, Khanh
Abstract : Computer-assisted orthopaedic surgery was born in the 1990s. Nowadays, computer-assisted orthopaedic surgery is used for transpedicular screw fixation and for total knee arthroplasty. Patient-specific instrumentation is one type of computer-assisted surgery based on volumetric images, such as computed tomography or magnetic resonance imaging. In this article, possible applications of patient-specific instruments in paediatric orthopaedics are described. The use of patient-specific instrumentation for the correction of cubitus varus is given as an example with complex osteotomy. Another application for tarsal coalition resection is shown. A last example of using patient-specific instrumentation for both tumour resection and allograft reconstruction is illustrated. Patient-specific instruments based on computed tomography of the bone can increase peri-operative accuracy and decrease operative time. They are very helpful for the surgeon. Other applications are possible and will be probably developed in the future. Cite this article: Docquier PL, Paul L, TranDuy V. Surgical navigation in paediatric orthopaedics. EFORT Open Rev 2016;1:152-159. DOI: 10.1302/2058-5241.1.000009.